Analisis Perspektif Akuntansi Lingkungan PT Sumber Graha Sejahtera Luwu - Sahrir, Sahrir; Sultan, Sultan; Syamsuddin, Sofyan; Riyanti, Riyanti (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2024)
This study aims to find out how the application of environmental accounting at PT Sumber Graha Sejahtera Luwu, as well as what are the cost components related to waste management, and how to treat environmental accounting. This research method uses qualitative research methods. Where the researcher describes the findings that come from the results of interviews, field observations, and documentation. The result of this research is that the company recognizes environmental costs by creating a Waste Management structure by recording transactions for B3 waste management which are then disclosed in the company's financial statements. Cost components related to waste management consist of land, buildings, machinery and IPAL structure equipment, as well as operational costs for waste management. The results showed that PT SGS had implemented environmental accounting, in practice the company had incurred environmental costs related to waste management and included it in the financial statements. The operational costs of waste management itself consist of labor costs, building maintenance costs, costs of spare parts and auxiliary materials, energy costs, retribution and testing costs, expedition and cleaning costs, and depreciation costs. The accounting treatment for waste management costs is in accordance with the relevant PSAK.